High-strain air-working soft transducers produced from nanostructured block copolymer ionomer/silicate/ionic liquid nanocomposite membranes - Lee, Jang-Woo; Yu, Seunggun; Hong, Soon Man; Koo, Chong Min (ROYAL SOC CHEMISTRY, 2013)
The present work demonstrates that nanostructured middle-block sulfonated styrenic pentablock copolymer ionomer (SSPB)/sulfonated montmorillonite (s-MMT) nanocomposite membranes, incorporating bulky imidazolium ionic liquid (IL), act as novel polymer electrolytes for air-working ionic polymer-metal composite (IPMC) actuators. The microphase-separated big-size ionic domains of the SSPB on the scale of several tens of nanometers and the role of s-MMT as an ionic bridge between the ion channels resulted in not only unexpectedly larger ion conductivity, larger air-working bending displacement and faster bending rate, without conventional IPMC drawbacks, including back relaxation and a sacrifice of mechanical strength, but also higher energy efficiency actuation than Nafion. Interestingly, the bending displacement, bending rate, and charge-specific displacement of the nanocomposite IPMC increased with the increase in bulkiness of the ILs because of the strong ion pumping effect of the bulky immidazolium cations in the size-matched big ion channels of the nanocomposite membrane.
Keywords: POLYMER-METAL COMPOSITES; RADIATION-GRAFTED FLUOROPOLYMERS; IONIC LIQUIDS; CARBON NANOTUBE; ACTUATORS; PERFORMANCE